Extracellular Vesicles Influence the Growth and Adhesion of Staphylococcus epidermidis Under Antimicrobial Selective Pressure - Zaborowska, Magdalena; Taulé Flores, Carles; Vazirisani, Forugh; Shah, Furqan A.; Thomsen, Peter; Trobos, Margarita (Frontiers in Microbiology, 2020)
Staphylococcus epidermidis causes infections associated with orthopedic implants due to its ability to establish persistent biofilms, making infections chronic and hard to treat. Extracellular vesicles (EVs) are part of the bacterial communication system, but the role of S. epidermidis-derived EVs in biofilm formation processes and survival is completely unknown. The aims of this study were i) to investigate the effect of subinhibitory concentrations of antibiotics on vesiculation in S. epidermidis and evaluate the role of EVs in bacterial survival and adhesion under antimicrobial selective pressure and ii) to evaluate whether EVs derived from a gentamicin-resistant S. epidermidis strain influence the susceptibility and adhesion of a gentamicin-susceptible strain. A gentamicin-susceptible (GENS) strain isolated from implant-associated osteomyelitis was cultured with EVs previously isolated from the same strain growing with subinhibitory concentrations of GEN (0, 0.03, 0.06 µg x mL-1) or with EVs from a gentamicin-resistant (GENR) strain. EVs were characterized regarding their size, number and protein content. The growth of S. epidermidis cultured with increasing concentrations of GEN (<=> MIC of 0.12 µg x mL-1) was recorded, viability was determined by quantitative culturing and fluorescence staining, and biofilm biomass on polystyrene was quantified by crystal violet staining. Cells grown in subinhibitory concentrations of GEN produced a larger number of EVs of similar size but with greater protein content than cells grown in control (Ctrl) conditions (0 GEN). Under antimicrobial pressure, EVs promoted different mechanisms of antimicrobial tolerance depending on the EV and GEN concentrations. Cell adhesion to polystyrene decreased in the presence of 0 and 0.03 µg x mL-1 GEN upon EV stimulation. Compared with Ctrl cells, cells treated with EVs from a GENR strain showed increased cell division during the exponential growth phase, faster maximal growth rate, shorter doubling time (8-33 min), and dramatically inhibited cell adhesion. These findings suggest that vesiculation in S. epidermidis is a survival response to subinhibitory concentrations of gentamicin. EVs may contribute to bacterial survival through their involvement (1) in the modulation of the growth rate, affecting cell division, and (2) in cell adhesion, decreasing cell attachment to polystyrene and glass.